ECONOMIC ASPECTS OF THE REGULATORY REQUIREMENTS IN THE DESIGN OF THE RECONSTRUCTION PLAN FOR TRANS-SHIPMENT POINTS - Korzhenevych, I. P.; Todua, T. H. (Science and Transport Progress, 2008)
The influence of normative requirements on the cost indices of plan reorganization is considered.